VirtumFi: Pengembangan Bahan Ajar Terintegrasi Android dan Soal HOTS pada Topik Gejala Kuantum untuk SMA - Kurniawan, Fatah; Sulur, Sulur; Pramono, Nugroho Adi; Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Kapıcı, Hasan Özgür; Darmawan, Alif (Universitas Negeri Surabaya, 2024)
Objective: One of the physics materials that are very important for students is quantum phenomena because it cannot be separated in everyday life. This research aims to develop a learning media